Legal Analysis of Civil Service Administration in Regional Government: Case Study of Central Lombok Regency, Indonesia - Wiredarme; M. Zaenul Muttaqin (Yayasan Hisnul Muslim Lombok, 2024)
This study examines the implementation of civil service discipline regulations in Central Lombok Regency, Indonesia, with a focus on Government Regulation No. 94 of 2021. Through analysis of legal frameworks, institutional structures, and empirical data on disciplinary actions, the research assesses the effectiveness of regulatory enforcement and identifies key factors influencing compliance. The findings reveal ongoing challenges in cultivating intrinsic adherence to disciplinary standards among civil servants, with extrinsic motivations and inconsistent rule application persisting as obstacles. This case study contributes to the broader discourse on public administration reform and the cultivation of good governance practices in decentralized systems.